Metode Euler-Milstein untuk Solusi Numerik Persamaan Diferensial Stokhastik Ornstein-Uhlenbeck - Taufik Iqbal; Muhammad Subhan (Journal of Mathematics UNP, 2020)
Abstract —The Ornstein-Uhlenbeck.equation is a stochastic differential equation, this equation.isoften used in the financial mathematical model. However, to find the solution the Ornstein Uhlenbeck equation.is.difficult.to complete analytic so it can also be solved by looking for numerical solutions. To get a better numeric solution it is required a numeric. method by. looking at converged. The purpose of the study is to examine. the Euler-Milstein method formula for the solution of the Ornstein-Uhlenbeck equation, shows that numerical solution of Ornstein-Uhlenbeck equation that resulted by Euler-Milstein.method has strong convergence. to exact solutions and create an algorithm to find the solution of Ornstein-Uhlenbeck equation with the Euler-Milstein method.Keywords — stochastic.differential.Equations, ornstein-uhlenbeck equation, euler- milstein method